MENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PENGUKURAN PANJANG DAN BERAT MELALUI PENGGUNAAN MEDIA TABEL KONVERSI SATUAN PADA SISWA KELAS II B SD NEGERI 016 TANJUNGPINANG TIMUR TAHUN PELAJARAN 2021/2022 - Muhammad Nur; Hairunnisa; MUTIA UTAMI (STAI Miftahul Ulum Tanjungpinang, 2023)
The low learning outcomes of class II students in the mathematics subject on the measurement of the length and weight became the background for this research. The purpose of this study was to determine the increase in mathematics learning outcomes in the material for measuring the length and weight using the media unit conversion table in class II B students at SD Negeri 016 East Tanjungpinang for the 2021/2022 academic year. This research is a classroom action research with the application of two action cycles consisting of planning, action implementation, observation, and reflection stages. The target of this research was Class II B students at SD Negeri 016 East Tanjungpinang for the academic year 2021/2022, a total of 31 people. The research data was obtained from observing learning activities and written test scores in the cognitive domain of students. The results of the research data analysis show that the use of unit conversion table media can improve students' mathematics learning outcomes. This is shown in the learning completeness score in pre-cycle only 10 students (32.26%) with an average score of 51.61 from the initial KKM score of 68. After the researcher used the unit conversion table media, student learning outcomes increased in cycle I with a score the average becomes 65.16 or students reach the KKM, namely 19 students (61.29%). The average score in Cycle II increased again to an average of 75.48 or students achieved the KKM score of 27 students (87.10%). Student learning outcomes increased by 23.87 points or 54.84% after getting two action cycles using unit conversion table media. This study concludes that there is an increase in the learning outcomes of Class II B students at SD Negeri 016 Tanjungpinang Timur in the subject of mathematics on the conversion of units of length and weight through the use of unit conversion tables as media